(untitled) (Training and Practice : Journal of Educational Sciences, 2018)
The number and ratio of retired age population reveals an increasing tendency all over the world. A pensioner in the 21st century will be able to plan ahead not only for 5-10 years but for a longer period of time. In many cases, longer life expectancy is accompanied by a sedentary lifestyle that may contribute to the emergence of several diseases, including cardiovascular diseases or musculoskeletal disorders in leading position. Regular physical and mental activity manifests itself as a significant factor of prevention that can decelerate physical and mental deterioration to a great extent. In addition to physical activity, healthy nutritional habits, the active use of leisure time, mental health and improving intellectual skills, as major components of a healthy lifestyle, are able to have a positive impact on the process of ageing, improvements in the quality of life, achieving a healthy level of fitness. In this study we want to highlight those activities that are able to support the key factors of maintaining and developing mental health, mental and physical activity and healthy nutritional habits, thus providing a meaningful, healthy lifestyle over the age of 60.